A276 TOTAL PANCREATIC LIPOMATOSIS AND EXOCRINE PANCREATIC INSUFFICIENCY IN A PATIENT WITH CELIAC DISEASE: AN UNUSUAL ENTITY. (26th February 2020) - Nassiri, S; Tomaszewski, M; Ou, G
Abstract: Background: Exocrine pancreatic insufficiency (EPI) is characterized by maldigestion and malabsorption of nutrients and is most commonly caused by diseases of the pancreatic parenchyma including chronic pancreatitis and cystic fibrosis (CF). However, EPI is also observed in other conditions including celiac disease (CD). Aims: We report a case of EPI in a patient with CD found to have total fatty replacement of the pancreas. Methods: A case report and review of the literature were performed. Results: Case Report: A 42-year-old man with CD on gluten-free diet (GFD) presented with a two-year history of increasing bowel frequency (4–6 times daily) and steatorrhea. Quantitative fecal fat over 72 hours confirmed fecal fat excretion of 101g/day; N < 7g) and total stool weight of 3761g. Nadir weight was 67.6 kg. There was a dramatic response to pancreatic enzyme replacement therapy (PERT) with marked improvement in bowel habits and weight gain to 74.8 kg over half a year. There is no history of pancreatitis, abdominal pain or alcohol abuse. He does not smoke but drinks 1–2 units of alcohol per week at most. Family history is negative for pancreatitis and pancreatic malignancy. On examination, following PERT, the patient appeared well-developed and nourished. He did not have clinical features or biochemical evidence of fat-soluble vitamin deficiency following PERT. Anti-tTG was equivocal (7.6 U/mL; N < 7 U/mL). IgG subclasses were normal. Chromogranin was mildly elevated (100mcg/L; N < 94mcg/L), but gastrin (15ng/L) and 24-hour urine for 5-hydroxyindoleacetate [5-HIAA] (23umol/d) were normal. Endoscopic evaluations including upper endoscopy, colonoscopy, and capsule endoscopy demonstrated intact duodenal villous architecture without inflammation, no microscopic colitis, and no small bowel mucosal disease, respectively. CT of the abdomen revealed total fatty replacement of the pancreas with no pancreatic parenchyma (Figure 1). Sweat sodium test was positive (67 mmol/L, N < 60 mmol/L) but CFTR gene sequencing was negative. There was no evidence of diabetes, hyperlipidemia, hyperferritinemia, Cushing's syndrome, or hepatic disease on biochemical investigations. Literature Review: Total pancreatic lipomatosis (TPL), or fatty replacement of the pancreas, is a rare cause of EPI which leads to maldigestion, malabsorption, and malnutrition. The pathogenesis of TPL is poorly understood but predisposing factors include obesity, diabetes mellitus, hyperlipidemia, malnutrition, Cushing's syndrome, hemochromatosis, chronic pancreatitis and CF. EPI can also manifest in patients with CD due to active small bowel inflammation or chronic pancreatitis. Last but not least, there appears to be higher prevalence of CD in CF patients. Conclusions: Persistent steatorrhea with weight loss despite GFD in patients with CD should prompt other considerations of EPI and trial of PERT. Funding Agencies: None